Indigenous storage practices and related traditional knowledge – A case study from Gujarat (India) - MUNJALSINH J PARMAR; B K JAIN (International Journal of Pharma and Bio Sciences, 2016)
Indigenous Knowledge (IK) can be defined as the foundation for the ethnic groups for grass root level decision making in the areas like food security, human and animal health, natural resource management, environment conversation and other vital economic and social activities. IK is the most significant tool that adds into the efficiency, effectiveness and sustainability of the development of the communities practicing that knowledge. The paper deals with the indigenous storage practices for grains, pulse, other agricultural products and food items. It also deals with the related traditional knowledge of those storage practices. The practices discussed in the paper are outcome of various extensive field excursions made within Gujarat state for past 4 years. The techniques and cases discussed in here shows immense traditional wisdom which these indigenous people have earned over generations and have added into it by trial and error. These practices are very easy to follow, ecofriendly, cost effective, and also increase shelf life of seeds. Hence, it is wise to promote these indigenous techniques to assure food security in the areas with tribal population. The findings include 11 different types of traditional storage containers, 5 different grain storage practices, and 5 traditional food preservation practices.